The Recreation of Gender Stereotypes in Male Cross-Dressing Performances on Douyin. Issue 5 (20th October 2021) - Tang, Xuan; Zou, Wenxue; Hu, Zhenchao; Tang, Lu
ABSTRACT: This article examines the performances of male cross-dressers on Douyin and its underlying cultural ideologies in neo/non-liberal China through critical discourse analysis. Our analysis of male cross-dressing performers' portrayal of female roles in mother-son/daughter relationships, heterosexual romantic relationships, and friendships shows that such performances highlight four stereotypical feminine characters: fragile, controlling, materialistic, and insincere. We conclude that traditional Chinese gender ideologies, commercialization, and the government's regulation have given birth to this apolitical form of comedy that portrays women as inferior to men and disciplines them to conform to traditional gendered roles.